The content of natural radionuclides Ra226, Th232, K40 in titanium ores and host rocks of the Pizhemskoye deposit - A. B. Makeyev (Известия высших учебных заведений: Геология и разведка)
Background. The value of natural radionuclide content in ores is a fundamental characteristic of any ore deposit, determining the possibility of studying, developing and enriching these ores, as well as manufacturing commercial products on their basis.Aim. To evaluate the content of natural radionuclides in the rocks and ores of the Pizhem titanium deposit and to determine their mineral concentrators.Materials and methods. A study of 15 core samples from wells within the Pizhem titanium deposit was carried out in the laboratories of IGEM RAS and VIMS using an “Ortec-65195-P/DSPecPlus” semiconductor gamma spectrometer.Results. For the first time, a radiation safety assessment was carried out and the concentration of Ra226, Th232 and K40 natural radionuclides in the titanium ores and host rocks of the Pizhemskoye deposit (the Middle Timan) was determined. The mineral concentrators for Ra226, Th232 and K40 were found to be zircon, monazite (kularite) and hydromuscovite-illite, respectively. The lowest content of radionuclides was established for quartz (D2pz) and quartz-kaolinite (PR3mr3) sandstones of glass quality. The titanium ores of the deposit belong to the I class of mineral raw materials (Aeff < 0.74 kBq/kg), thereby being completely harmless to humans.Conclusion. The low content of radionuclides in the studied ores allows them to be safely enriched, and the overburden sandstones of glass quality to be used without restrictions.